(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
This study aimed to find out the effect of plyometric training on improving values of some kinematics variables of high-jump shooting skill and accuracy in Handball. The researcher used the single group experimental design. The research sample was the players of Naft Al-Janoob Club, season 2020- 2021, they were chosen intentionally. The researcher photographed the research sample using a camera. “Sony” (250 images/sec), And he conducted the kinematic analysis using the “dart-fish” program. The implementation of the proposed training curriculum continued for (8) weeks at (24) training units and a rate of (3) training units per week. The researcher took into account the time specified for each training unit and the number of training units per week, and the general capabilities of the players, as well as the availability of devices and tools, as the researcher was ensured that the curriculum vocabulary is consistent with the scheduled exercises prepared previously for the team. the researcher concluded that there was an improvement in the values of kinematics variables while applying the plyometric training through the results of pre and posttests and for the favor of posttest, as well as the used training method that included plyometric training improved the shooting accuracy performance in high shooting in the post-test due to the use of the same exercises of the motor pathway. The researcher recommended using plyometric training to develop the values of kinematics variables of high-jump shooting skill.